NEW EDUCATION PROGRAM IN VALUES EDUCATION: TÜRKİYE CENTURY MAARIF MODEL - Dila Can, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In 2024, Türkiye put into effect the Türkiye Century Maarif Model Curriculum, which was completed in 2023. The curriculum has sparked significant debate since its publication. Each discipline has contributed its own perspectives, leading to extensive discussions on the subject. The main reason for the most vocal debate is the title and principle of the Maarif Model for the Turkish Century. The name Maarif has not been heard in Türkiye for a long time, and as a model, it was put forward for the first time in 2024. The most striking point of the Maarif Model education is the perspective it develops in terms of values education. This perspective integrates the targeted human model and philosophy into all curricula in Türkiye. Maarif Model, which is examined within the framework of values education, was analyzed in this study in order to understand its basic elements, present its disciplines and explain its impact for Türkiye. Document analysis, one of the deductive analysis approaches, was used as a method in the study. The entire study was selected from the “Common Text of Curriculum” published by the Ministry of National Education of the Republic of Türkiye and translated into English.